Pressure effects on the stability of lipoxygenase: Fourier transform-infrared spectroscopy (FT-IR) and enzyme activity studies - Heinisch, Oliver; Kowalski, Elisabeth; Goossens, K.; Frank, J.; Heremans, K.; Ludwig, Horst; Tauscher, Bernhard (Zeitschrift für Lebensmittel-Untersuchung und -Forschung. A, European food research, 1995)
Fourier transform infrared spectroscopy (FT-IR) studies of lipoxygenase at pressures of up to 1.2 GPa have shown changes in the amide I' band which correlate to structural changes of the enzyme. The shift of the frequency maximum of the amide I' band at about 600 MPa suggests a cooperative change in the secondary structure of the protein. Studies of the changes in band width have shown the structural changes at 600 MPa to be irreversible. This has been confirmed by studies of enzyme activity after pressure treatment: exposure to 600 MPa for 30 min (40 degrees C) clearly reduced the activity of lipoxygenase. Anodic gel electrophoresis under non-denaturating conditions revealed a decrease in native protein parallel to the activity loss. A pressure-temperature-phase diagram for soybean lipoxygenase was established.
Gesehen am 15.01.2026